1977
DOI: 10.1111/j.2042-7158.1977.tb11521.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by Metoclopramide of Responses to Cholinergic Nerve Stimulation in the Isolated Gastric Fundus Preparation of the Rat

Abstract: y b o t h a s an a n t i -e m e t i c and a l s o t o i n c r e a s e t h e r a t e o f g a s t r i c emptying ( P i n d e r g! o t h e r s , 1 9 7 6 ) . The a n t i -e m e t i c e f f e c t o f metoclopramide is p r o b a b l y r e l a t e d t o i t s a c t i o n i n b l o c k i n g dopamine r e c e p t o r s ( p e r i n g e r & o t h e r s , 1975; Day & Blower, 1 9 7 5 ) . However, t h e mechanism o f i t s a c t i o n on t h e g a s t r o i n t e s t i n a l t r a c t i s n o t c l e a r and a number of p o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Many observations concur that the drug facilitates spontaneous and stimulation-evoked release of acetylcholine (ACh) but a possible postjunctional sensitization of the smooth muscle cells to this neurotransmitter remains controversial Bianchi et al, 1970;Fontaine & Reuse, 1972;1973;Bury & Mashford, 1976;Anderson et al, 1977;Kilbinger et al, 1982;Zar et al, 1982;Massingham et al, 1985). Fox et al (1983) have recently demonstrated that surfactants can selectively ablate enteric neurones in the ratjejunum.…”
Section: Introductionmentioning
confidence: 99%
“…Many observations concur that the drug facilitates spontaneous and stimulation-evoked release of acetylcholine (ACh) but a possible postjunctional sensitization of the smooth muscle cells to this neurotransmitter remains controversial Bianchi et al, 1970;Fontaine & Reuse, 1972;1973;Bury & Mashford, 1976;Anderson et al, 1977;Kilbinger et al, 1982;Zar et al, 1982;Massingham et al, 1985). Fox et al (1983) have recently demonstrated that surfactants can selectively ablate enteric neurones in the ratjejunum.…”
Section: Introductionmentioning
confidence: 99%